Dark Utopia: Or sleeping through Marten Spångberg's Natten. (16th November 2020) - Rutgeerts, Jonas
Abstract : In 'Dark Utopia, Or Sleeping Through Marten Spångberg's Natten ' Jonas Rutgeerts explores the utopian potential of Marten Spångberg's performance Natten (2016). Contrary to traditional utopian artworks, Spångberg's piece does not depict a specific image of a brighter future, or a set of instructions that we should follow in order to make the world a better place. On the contrary, the piece blatantly refuses to give the spectator any concrete directions. It does not produce a beacon of light that guides us, but celebrates darkens, unfolding like a dreamscape in which different atmospheres continuously blend together. Natten produces an undulating movement that sets the audience adrift. However, in this article I will argue that the utopian potential of this piece should be connected to these unbecoming moments when the audience gets lost. Here the spectator is able to lift the present out of its temporal chackels and to explore the potential of spending time together. Drawing form the work of Félix Guattari and Gilles Deleuze I connect this experience to the conceptualization of an 'immanent utopia'. That is, a utopia that is no longer geared towards an abstract future, but allows us to focus on the particularity of the present and to explore the utopian potential that is engrained into this present.